Household chores and household choices : theorizing the domestic sphere in historical archaeology - Barile, Kerri S.; Brandon, Jamie C. (University of Alabama Press, 2004)
The time is ripe for such an effort, as the questions that gather under the labels of modernity, the postmodern, and critical theory now transcend a single discipline. The work of John Rawls on justice in public life has had a generation of influence on scholarship, and this work seems to have a high degree of likelihood of making meaningful statements on these questions in the field.
Keywords: Historic sites -- United States.; Material culture -- United States.; Landscapes -- Social aspects -- United States -- History.; Households -- United States -- History.; Families -- United States.; Sex role -- United States -- History.; Archaeology and history -- United States.; Feminist archaeology -- United States.; Archaeology -- Methodology.; United States -- Antiquities.; Culture matérielle -- États-Unis.; Paysages -- Aspect social -- États-Unis -- Histoire.; Ménages (Statistique) -- États-Unis -- Histoire.; Familles -- États-Unis.; Rôle selon le sexe -- États-Unis -- Histoire.; Archéologie et histoire -- États-Unis.; Féminisme et archéologie -- États-Unis.; Archéologie -- Méthodologie.; États-Unis -- Antiquités.; HOUSE & HOME -- Reference.; FAMILY & RELATIONSHIPS -- General.; Antiquities; Archaeology and history; Archaeology -- Methodology; Families; Feminist archaeology; Historic sites; Households; Landscapes -- Social aspects; Material culture; Sex role; United States; Haushalt; Archäologie; Ausgrabung; Geschichte; Lebensbedingungen; Siedlung; USA; History